Accelerator ELV-12 and its applications in environment protection technologies - Veis, M.E.; Golubenko, Yu.I.; Kuksanov, N.K.; Nemytov, P.I.; Prudnikov, V.V.; Salimov, R.A.; Fadeev, S.N. (Вопросы атомной науки и техники, 2004)
For the environment protection purposes, at BINP we developed, designed and manufactured an accelerator ofa new
generation ELV-12 with the following parameters: electron energy ranges from 0.6 to 1.0 MeV, beam current is up to
400 mA, beam power up to 400 kW. At present, the accelerator is already manufactured, assembled and all the systems
are under adjustment and test. Для природоохоронних застосувань ІЯФ СВ РАН розробив і виготовив прискорювач нового покоління
ЕЛВ-12 з наступними параметрами: енергія електронів 0.6...1.0 МеВ, струм пучка до 400 мА, потужність
пучка до 400 кВт. В даний час прискорювач виготовлений, зібраний, ведеться налагодження його систем і
тестування. Для природоохранных применений ИЯФ СО РАН разработал и изготовил ускоритель нового поколения
ЭЛВ-12 со следующими параметрами: энергия электронов 0.6…1.0 МэВ, ток пучка до 400 мА, мощность
пучка до 400 кВт. В настоящее время ускоритель изготовлен, собран, ведется отладка его систем и тестирование.